The clinical picture presented by the sick child and its value in estimating progress - Craig, Wiliam Stuart (The University of Edinburgh, 1931)
The primary object of the foregoing remarks has been to emphasise the immense value of a close observation of the young patient. With this in view the method has been to attempt to give an impression of the pictures presented by various patients as they changed from day to day, to explain the method of arriving at conclusions, and to correlate them with the clinical findings and course of the case. Graphical expression of the findings has also been appended, which will be found to show

(i) In many cases day to day changes in the appearance and demeanour of the patient occurred almost simultaneously with other changes in physical findings. (ii) In certain conditions a careful general observation of the patient allowed of sa earlier appreciation of the course of the illness than could be obtained from any other forms of investigation. (iii) In a few isolated instances a study of the child's behaviour, activities and outlook confirmed aaimpression of marked improvement not suggested by more scientific lines of enquiry.

The cases considered throughout have all been under observation in hospital, but there is no evident reason why the watching of patients along similar lines in private practice should not carry with it the same results and advantages, and these it is suggested include: -

(i) Frequently, a readier appreciation of the gravity of the child's condition at the outset. (ii) A fairly accurate surmise as to any alteration for good or bad before any detailed examination is commenced. (iii) A basis for qualified prognosis in certain cases, even in the absence of diagnosis. (iv) In acutely severe cases of certain types the acquiring of sufficient information regarding the patients state without the disturbance of frequent examination. (v) The unconscious acquirement of a sympathetic understanding of the child's feelings, leading to a more intimate and more natural reaction between patient and attendant.

It is neither possible nor desirable to lay down hard and fast rules as to how this form of clinical observation may be acquired. An arbitrary grouping of clinical conditions was necessary when discussing the question, but actually in the application of the subject of the paper, there can be no set method nor rigid formulary method of approach. On each occasion the individual factor arises both in regard to patient and clinician, and there lies the line of research. The medical has to study for himself his own attitude towards children of all ages as-they differ from adults, to learn for himself how children react towards him, and finally, allowing for these two factors to develop the power of first of all seeing all that exists in the picture the child presents, and then afterwards interpreting the significance of each detail in that picture. Once capable of that then, the clinician can utilise purely laboratory findings to better purpose, and eventually pursue a line of scientific investigation without ever forgetting the him individuality and personality of the children providing/with his material.
The clinical picture presented by the sick child and its value in estimating progress: submitted for the Thomson Memorial Medal, 1931